Developing a Conceptual Model of Learning Analytics in Serious Games for STEM Education - Zaki, N. A. A.; Zain, N. Z. M.; Noor, N. A. Z. M.; Hashim, H. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
Utilizing serious games as teaching aid can stimulate students’ interest in learning and enhancing students’ understanding of STEM learning. The use of serious game on learning analytics for STEM learning provides assessment data to measure students’ performances and achievements of predefined learning outcomes. While numerous researches on learning analytic in serious games have been conducted, studies on their association with STEM learning are scarce. Past studies also indicate that teachers use serious games in teaching but yet to utilize serious games as assessment tools. This situation leads to the need of developing a conceptual model of learning analytics in serious games for STEM education (APPS-STEM). The conceptual model was initially developed through the focus group approach and literature review to examine the learning metrics of serious games, which is appropriate for STEM learning before being verified by experts. Based on the result from expert review, the conceptual model of APPS-STEM contains nine themes, namely effectiveness, problem-solving thinking and creativity, flexibility, key stakeholders, emotions, serious game design, curriculum profiles, learning profiles, and target user norms. This conceptual model is expected to serve as a guide for stakeholders to implement learning analytics in serious games design for STEM learning. Further study will be the development of serious game prototypes to determine the effectiveness of the APPS-STEM model in the STEM learning paradigm.